Experimental and numerical investigation of micro-scale effusion and transpiration air cooling on cascaded turbine blades - Kim, Mingeon; Shin, Dong Hwan; Lee, Bong Jae; Lee, Jungho (Case Studies in Thermal Engineering, 2022)
Micro cooling utilizing the micro-sized cooling hole or a porous structure on the surface is a promising technology in cooling applications of gas turbine blades. Although there have been numerous parametric studies on basic geometries to enhance the performance of micro cooling, little has been done for experimental study on blade geometry. This study comprehensively investigated micro cooling performance by applying effusion and transpiration cooling to C3X blades arranged in a cascade. The overall cooling effectiveness distribution on the blade surface was estimated by using infrared thermometry. In addition, the velocity and thermal boundary layer formation by cooling air were qualitatively investigated by a flow visualization using the smoke-laser sheet technique and numerical simulation using the shear stress transport k-ω turbulence model. Micro cooling performs effectively because of the convective heat transfer through the microstructure of the blade wall but also the reduction of heat transfer from the hot mainstream due to the formation of a uniform coolant layer on the blade surface. Especially at the mass flow ratio of 5.3% used for typical gas turbine cooling, effusion cooling and transpiration cooling achieve the overall cooling effectiveness of 0.4 and 0.6, respectively.
Keywords: Air cooling; Blade Surface; Cascade blades; Effusion cooling; Experimental investigations; Infrared thermometry; Micro cooling; Numerical investigations; Overall cooling effectiveness; Transpiration cooling; Cascade blades; Effusion cooling; Gas turbine; Infrared thermometry; Transpiration cooling